Efeito do “Treino Cognitivo” na competência diagnóstica da dor torácica em estudantes de Medicina - OLIVEIRA, J. C. V. (2018)
Introduction: Clinical reasoning is the cognitive process that allows the physicians to make a diagnostic for a clinical case. Despite its great importance, there are few studies about teaching methods of this expertise that is really effective and that could define what is the best instructional approach for it. Most of the studies are based on scripts of diseases for the student to learn clinical reasoning. Objectives: To evaluate the effect of "Cognitive Training" on the diagnostic competence of diseases with chest pain as clinical manifestation in medical students. Materials and methods: This is an experimental study with 3 phases, in 18 medical students in third year of UNIFENAS-BH. On the initial assessment, phase 1, the students solved, individually, a group of 8 clinical cases (six of chest pain and two to distract) lasting 60 minutes. In the training, phase 2, the students were split, randomly, into two groups (Group 1 and 2). Group 1 was trained for herpes zoster, pericarditis and pulmonary thromboembolism and Group 2 for heart attack, gastroesophageal reflux and aortic dissection. This lasted 5 hours. After a week, in the final assessment, phase 3, all the students solved, individually, a new group of 10 clinical cases (six of chest pain with the same diagnostic in phase 1, two new cases to distract, and two new diagnostics of chest pain that hadn´t been trained on phase 2) lasting 60 minutes. The time spent in each case for resolution was measured and noted by participants in phase 1 and phase 3 of the study. The diagnostic accuracy was evaluated by the Mann-Whitney test according to each block studied, and in general by the Wilcoxon test. Results: both groups improved the rate of the diagnostic scores between phases 1 and 3 only for the trained diagnoses, not occurring the phenomenon of learning transfer. (Group 1, p = 0.004 and Group 2, p = 0.041). Conclusions: The instructional strategy of "cognitive training" was able to improve the diagnostic accuracy of medical students for diseases with chest pain as clinical presentation. However, the improvement occurred only for trained diseases, therefore, the phenomenon of learning transfer was not observed. The proposed strategy seems to take a positive effect on the accuracy diagnostic, it is easy to implement and can be considered for the teaching and development of clinical reasoning on the graduation courses.